Integrasi ESG dan Akuntansi Keberlanjutan dalam Mewujudkan Tujuan Pembangunan Berkelanjutan (SDGs): Studi Kasus Pada PT Bank Negara Indonesia (Persero) Tbk (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to analyze how PT Bank Negara Indonesia (Persero) Tbk (BNI) adopts and integrates Environmental, Social, and Governance (ESG) principles into its sustainability accounting practices as part of its contribution to achieving the Sustainable Development Goals (SDGs). Utilizing a descriptive qualitative approach with a case study method, this research examines BNI’s annual and sustainability reports. The findings reveal that BNI actively applies ESG principles through GRI-based reporting, stakeholder engagement, and the development of green initiatives in both financing and operations. Its programs are aligned with specific SDG targets, particularly in financial inclusion, MSME empowerment, and sustainable financing. BNI’s sustainability accounting not only reflects financial performance but also captures measurable and transparent social and environmental outcomes. These results underscore the importance of ESG integration in corporate reporting, especially within Indonesia's banking sector in support of sustainable development.